The rise and fall of the Italian economy - Bastasin, Carlo 1959-; Toniolo, Gianni 1942-2022 (Cambridge University Press, 2023)
"Carlo Bastasin and Gianni Toniolo provide a much-needed, up-to-date economic history of Italy from unification in 1861 to the present. They reveal the factors behind Italy's twentieth-century growth as well as how economic decline in the last thirty years has resulted in rising levels of populism, mistrust and government instability"--
Includes bibliographical references
Keywords: Geschichte 1861-2022; Wirtschaft; Italien; Italy / Economic conditions / 1945-; Italy / Economic conditions / 1918-1945; Italy / Economic conditions / 1870-1918; Italy / Economic policy; Italy / History; Italy / Politics and government